THE EFFECT OF ROA, DER, AND OPM ON STOCK RETURNS OF NON-CYCLICAL CONSUMER COMPANIES - Young Pao; Ira Grania Mustika; Syarbini Ikhsan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to find out how significant the influence of Probability through the variables Return on Assets, Operating Profit Margin, and Leverage through the Debt To Equity Ratio variable is on stock returns in non-cyclical consumer sector companies on the Indonesia Stock Exchange (BEI) in 2019-2023. The sample that met the inclusion criteria was 28 companies with a total of 129 data using purposive sampling techniques. This research uses classical assumption tests such as normality, multicollinearity, autocorrelation, and heteroscedasticity. Followed by multiple linear regression tests, coefficient of determination, t and f model tests then hypothesis testing. Data processing uses the SPSS version 27 program. The results of this study show that partially the variables Return on Assets and Debt to Equity Ratio have a significant influence on stock returns but the Operating Profit Margin variable has an insignificant influence on stock returns. This research also reveals that the variables Return on Assets, Operating Profit Margin, and Debt To Equity Ratio have an influence on stock returns simultaneously.